PENGARUH KONSERVATISME AKUNTANSI TERHADAP NILAI PERUSAHAAN PADA KRISIS KEUANGAN TAHUN 2008 - Hartono, Rizkita Amalinda; Sabeni, Arifin (Diponegoro Journal of Accounting, 2014)
The study aims to examine the effects of accounting conservatism applied by public companies before the crisis period on firm value in crisis period. In this study, accounting conservatism is measured by C-Score and shareholder’s value is measured by three proxies, which are buy-and-hold abnormal return (BHAR), cumulative stock return, and stock return volatility. Beta, cash holdings, sales growth, and tangibility are used as control variables. The population of this study is all the public companies listed in Indonesia Stock Exchange (IDX) in 2003-2009. The sampling method used is purposive sampling. Total data of this study is 303 companies. Then 59 data that include outliers should be excluded from samples of observation. So the final samples are 244 data. Multiple regression is used as analysis technique. The empirical result of this study shows that accounting conservatism has positive and significant effects to both firm value proxies which are BHAR and cumulative stock return, meanwhile has negative and significant effect to stock return volatility. In sum, accounting conservatism has significant effect to shareholder’s value.